INSTITUTIONAL ASPECTS OF REGIONAL INNOVATION SYSTEMS DEVELOPMENT - I. Novikova; S. Rudich (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the study of the institutional component of the regional innovation syste of the Stavropol territory. It defines the structure of institutions, the role of institutions in the regional innovation system( RIS), and the impact of institutions on the effectiveness of RIS development. The content of RIS institutions in the Stavropol territory is analyzed. It is shown that, in addition to the weakness of the formal institutions of the innovation system in the region, informal institutions, which in the Stavropol region include corruption and cronyism, have a great influence on the development of RIS. Moreover, informal institutions significantly hinder the development of not only the regional innovation system, but also the economic complex of the region as a whole.